2016
DOI: 10.1002/arch.21330
|View full text |Cite
|
Sign up to set email alerts
|

LARVAL X‐RAY IRRADIATION INFLUENCES PROTEIN EXPRESSION IN PUPAE OF THE ORIENTAL FRUIT FLY, BACTROCERA DORSALIS

Abstract: The sterile insect technique (SIT) was developed to eradicate the new world screwworm from the southern United States and Mexico, and became a component of many area-wide integrated pest management programs, particularly useful in managing tephritid fruit flies. SIT is based on the idea of rearing and sterilizing male pests, originally by ionizing radiation, and then releasing into field, where they compete for and mate with wild females. Mating with sterile males leads to reduced fecundity to lower pest popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Radiation may induce physiological changes involving reduced phenoloxidase action in tephritid larvae. This was reported in larvae of Anastrepha suspensa (Loew) (Nation et al ., 1995), C. capitata (Mansour and Franz, 1996), and Bactrocera dorsalis (Hendel) (Chang et al ., 2016). Nevertheless, the qualitative determination of melanization is not feasible in all Anastrepha species, because observations in A. ludens larvae did not provide evidence of melanin in both D. crawfordi and U. anastrephae eggs and larvae as a signal of the host's immunological reaction (Cancino et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation may induce physiological changes involving reduced phenoloxidase action in tephritid larvae. This was reported in larvae of Anastrepha suspensa (Loew) (Nation et al ., 1995), C. capitata (Mansour and Franz, 1996), and Bactrocera dorsalis (Hendel) (Chang et al ., 2016). Nevertheless, the qualitative determination of melanization is not feasible in all Anastrepha species, because observations in A. ludens larvae did not provide evidence of melanin in both D. crawfordi and U. anastrephae eggs and larvae as a signal of the host's immunological reaction (Cancino et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was shown that old larvae of Anastrepha suspensa (Loew) produce large amounts of ecdysone hormone, which negatively affects the normal development of the parasitoid within the host (Lawrence, 1991). Experiments where development times of A. ludens pupae coming from irradiated larvae and from non‐irradiated ones were compared showed that the first larvae require more time to reach the pupal stage (Chang, Goodman, Ringbauer, Geib, & Stanley, 2016; Nation, Smittle, Milne, & Dykstra, 1995). This occurrence may well be an indicator of a certain handicap in producing ecdysone hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of 30, 40, and 50 Gy, applied to eggs and to first and second instar larvae, were effective in suppressing the emergence of adult flies, and the delay in host pupation observed at 72 h was only significant when radiation was applied to eggs. This effect was also reported on third instar larvae of B. dorsalis (Balock et al ., 1963; Chang et al ., 2016), with no negative repercussions for the development of parasitoids (Yulo-Nazarea and Marroto, 1993; Cancino et al ., 2009 b ). Irradiation affects the pupal development of the host, but is independent of the physiology of the parasitoid (Nation et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%